Electronic grade lead titanate and preparation method thereof
Through the sol-gel method and the use of composite surfactants, electronic grade lead titanate with high purity, uniform particle size and good dispersion were successfully prepared, which solved the problem of poor preparation quality of lead titanate in the prior art and expanded its application field.
Patent Information
- Application Number
- CN202411299162.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-09-18
AI Technical Summary
The existing lead titanate preparation method is difficult to obtain nano-lead titanate with high purity, uniform particle size and good dispersion, which limits its application in high-temperature PTC components and other fields.
By using the sol-gel method, electron-grade lead titanate is mixed with a solution of tetrabutyl titanate and lead acetate and added composite surfactant to adjust the pH and temperature, control the formation and growth process of crystal nuclei, and then aged, dried, ground and calcined, and finally obtained electronic grade lead titanate by washing and drying.
The prepared lead titanate has the characteristics of high purity, high dispersion, small particle size and narrow particle size distribution, which expands its application range in electronic components and other fields.
Smart Images

Figure CN119080060B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lead titanate, and in particular relates to electronic grade lead titanate and a preparation method thereof. Background Art
[0002] With the continuous expansion of the application fields and scope of materials, nanomaterials science and technology, as the product of human understanding of the microscopic world, has received extensive attention and research. Nanomaterials have shown special and excellent properties that are different from large-size materials in many fields due to their quantum size effects and surface effects, which directly determine the development of certain fields. For example, widely used semiconductor materials directly determine the development of integrated circuits, battery materials in the new energy field directly determine the development of battery technology, and piezoelectric materials, magnetic materials, hydrogen storage materials, optoelectronic materials, etc. all determine the development of their respective fields. Research in recent years has shown that the performance of nanomaterials is not only related to its size, but also closely related to its morphology and structure. Therefore, how to control the size, morphology, purity, etc. of materials has become the focus of research on nanomaterials.
[0003] PbTiO3 is a typical ferroelectric with excellent ferroelectric, piezoelectric, withstand voltage and pyroelectric properties. It has a high Curie temperature, a large electromechanical coupling coefficient and a small dielectric constant. There is a large anisotropy (0.49) between the transverse and longitudinal electromechanical coupling coefficients. It can be used to make high-frequency filters, ultrasonic transducers, infrared detectors, etc. It can also be used as a pigment component in paint formulations to improve the stability and durability of outdoor coatings. Therefore, it has attracted widespread attention and is a piezoelectric material with very broad application prospects.
[0004] In the field of electronic components, ultrafine PbTiO3 powder is widely used in the manufacture of high-temperature PTC (positive temperature coefficient thermistor). To prepare high-quality, durable and stable high-temperature PTC components, high-purity ultrafine PbTiO3 powder must be prepared. At present, the synthesis methods of nano lead titanate powder include solid phase method, gas phase method and liquid phase method. Among them, the liquid phase method includes precipitation method, hydrothermal method and sol-gel method. Solid phase lead titanate can be prepared by high-temperature solid phase reaction of lead oxide and titanium dioxide. However, the microscopic uniformity of lead titanate prepared in this way is very poor. Due to the use of mechanical mixing, the uniformity is poor. The PbO / TiO2 molar ratio is difficult to be 1:1 at the microscopic level, and PbO will volatilize at high temperature, affecting the quality and purity of lead titanate. Sol-gel method has become one of the most effective methods for preparing high-quality nano PbTiO3 with excellent performance due to its advantages of low reaction temperature, high product purity, uniform mixing, easy doping and low sintering temperature.
[0005] Chinese patent application CN102303903A discloses a method for preparing high-purity lead titanate. The specific steps of the preparation method are: adding lead acetate to a methanol solution at a weight ratio of 1:2 to dissolve, adding tetrabutyl titanate to an anhydrous ethanol solution at a weight ratio of 0.5-0.6:1 to dissolve, and then stirring and mixing the two solutions to obtain solution A; heating solution A and adding it to an ammonia solution (concentration is 25-28wt%), and adding hydrogen peroxide solution at the same time, and a dark yellow precipitate is generated; using the pH of the ammonia solution, stirring, filtering and precipitating, washing, to neutrality, to obtain solution B; drying solution B, grinding and calcining, and obtaining light yellow high-purity lead titanate. The preparation method of the high-purity lead titanate of the present invention has advanced synthesis technology, easy control of the reaction process, high effect and efficiency, and the obtained lead titanate has high purity and low impurities, and can be widely used in the market. However, it is not possible to see from the specification of the patent what the size, morphology, and purity of the lead titanate prepared are, and it is impossible to apply it to high-temperature PTC components.
[0006] Therefore, developing a method for preparing electronic-grade nano-lead titanate in this field is of great significance to expanding the application field of lead titanate. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing electronic grade lead titanate. The lead titanate prepared by the method has high purity, small particle size, large specific surface area, and expanded application fields of lead titanate.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] A method for preparing electronic grade lead titanate comprises the following steps:
[0010] S1. Add tetrabutyl titanate into ethanol and stir evenly to obtain a tetrabutyl titanate solution;
[0011] S2, adding lead acetate into deionized water and stirring evenly to obtain a lead acetate solution;
[0012] S3, adding the lead acetate solution in step S2 to the tetrabutyl titanate solution in step S1, then adding a composite surfactant, adjusting the pH, stirring and reacting, and obtaining a sol after the reaction is completed;
[0013] S4, aging, drying, grinding, calcining, and then washing and drying the sol in step S3 to obtain the electronic grade lead titanate.
[0014] Preferably, the concentration of the tetrabutyl titanate solution in step S1 is 0.5-1 mol / L.
[0015] More preferably, the concentration of the tetrabutyl titanate solution in step S1 is 0.6-0.8 mol / L
[0016] Preferably, the concentration of the lead acetate solution in step S2 is 0.25-0.5 mol / L.
[0017] More preferably, the concentration of the lead acetate solution in step S2 is 0.3-0.4 mol / L.
[0018] Preferably, in step S3, the volume ratio of the tetrabutyl titanate solution to the lead acetate solution is 100-200:200-400; the amount of the composite surfactant added is 2-4% of the mass of the tetrabutyl titanate solution; the pH is 3-5, the temperature of the stirring reaction is 50-60°C, and the time is 8-12h.
[0019] More preferably, in step S3, the volume ratio of the tetrabutyl titanate solution to the lead acetate solution is 150-200:300-400; the amount of the composite surfactant added is 2-3% of the mass of the tetrabutyl titanate solution; the pH is 3-4, the stirring reaction temperature is 55-60°C, and the time is 8-10h.
[0020] Preferably, the method for preparing the composite surfactant in step S3 comprises the following steps:
[0021] Glutamic acid is added into deionized water, followed by 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, and N-hydroxysuccinimide and hydroxypropyl chitosan are added after stirring for 30-50 minutes, and a heating reaction is carried out. After the reaction is completed, sodium dodecylbenzenesulfonate and docosanoic acid are added, and a constant temperature reaction is carried out. After the reaction is completed, the mixture is concentrated under reduced pressure to 1 / 4 of the volume, and then anhydrous ethanol is added for precipitation, followed by filtering, washing, and drying to obtain modified chitosan; the modified chitosan, hexadecyltrimethylammonium bromide, and citric acid are uniformly mixed to obtain the composite surfactant.
[0022] In the present invention, glutamic acid is first activated, and then hydroxypropyl chitosan is added to react with glutamic acid. Hydroxypropyl chitosan contains a large amount of amino hydroxyl groups, which can control the growth and crystallization process of lead titanate. Then sodium dodecylbenzene sulfonate and docosanoic acid are added. Sodium dodecylbenzene sulfonate is used as an emulsifier to make docosanoic acid evenly dispersed and improve reaction efficiency. Docosanoic acid is introduced into chitosan to convert part of the modified chitosan into hydrophobicity, thereby weakening the agglomeration of lead titanate during crystallization.
[0023] Preferably, the mass ratio of glutamic acid, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide, hydroxypropyl chitosan, sodium dodecylbenzene sulfonate and docosanoic acid is 10-20:20-30:20-30:40-50:3-5:15-25; the temperature of the heating reaction is 60-80°C, and the time is 2-4h; the temperature of the constant temperature reaction is 80-90°C, and the time is 2-3h.
[0024] Preferably, the mass ratio of the modified chitosan, hexadecyltrimethylammonium bromide and citric acid is 5-8:2-4:3-5.
[0025] In the present invention, hexadecyltrimethylammonium bromide is a commonly used cationic surfactant, which can provide strong surface activity and emulsification ability, thereby regulating the morphology and particle size of lead titanate.
[0026] In the present invention, citric acid and modified chitosan have a large number of amino groups and carboxyl groups, both of which have the ability to chelate metal ions and can coordinately regulate the crystallization process of lead titanate.
[0027] Preferably, the aging temperature in step S4 is 30-40° C. and the time is 16-20 h; the calcination temperature is 600-700° C. and the time is 2-3 h.
[0028] More preferably, the aging temperature in step S4 is 35-40° C. and the time is 16-18 h; the calcination temperature is 650-700° C. and the time is 2-2.5 h.
[0029] Preferably, the washing process in step S4 is: add 20-30 times the weight of lead titanate to a 1-3% disodium EDTA aqueous solution, stir and immerse for 40-60 minutes, filter and then wash with deionized water for 3-5 times; the drying temperature is 100-110°C, and the drying time is 3-4 hours.
[0030] More preferably, the washing process in step S4 is: adding 25-30 times the weight of lead titanate to a 1-3% disodium EDTA aqueous solution, stirring and immersing for 50-60 minutes, filtering and then washing with deionized water for 4-5 times; the drying temperature is 100-105°C, and the drying time is 3.5-4h.
[0031] In the present invention, the excellent chelating ability of disodium EDTA is utilized to allow disodium EDTA to chelate with metal ions adsorbed on the surface of lead titanate, thereby removing metal ion impurities remaining in the lead titanate and improving the purity of the product.
[0032] The present invention also protects electronic grade lead titanate prepared by the method as described above.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] (1) The preparation method of electronic grade lead titanate provided by the present invention is to prepare electronic grade lead titanate by a sol-gel method. At the same time, a composite surfactant is added during the preparation of the sol. On the one hand, it affects the rate of hydrolysis and polycondensation reaction, thereby controlling the nucleus formation and growth process, so that the prepared lead titanate has a uniform particle size. On the other hand, the surfactant can reduce the surface tension between particles and prevent particle agglomeration, so that the prepared lead titanate has good dispersibility. The composite surfactant can also control the reaction process, reduce the formation of by-products, and thus improve the purity of the lead titanate. Finally, through calcination and washing, the lead titanate has the characteristics of high purity, high dispersibility, small particle size and narrow distribution.
[0035] (2) The preparation method of electronic grade lead titanate provided by the present invention comprises adding a specific composite surfactant, stirring glutamic acid and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide to activate the carboxyl group thereof, and then reacting with hydroxypropyl chitosan, so that glutamic acid and hydroxypropyl chitosan are combined in the form of a covalent bond, and then reacting with docosanoic acid to introduce a hydrophobic long-chain alkyl group into the hydroxypropyl chitosan to obtain modified chitosan. Glutamic acid, as an acidic amino acid, can be adsorbed on the surface of the crystal nucleus to inhibit excessive growth, and also forms a complex with titanium or lead ions to control the particle size of the lead titanate; hydroxypropyl chitosan Sugar contains a large number of hydroxyl and amino groups, which can interact with titanium or lead ions, thereby controlling the particle size and morphology of lead titanate crystals; the composite surfactant can be adsorbed on the surface of lead titanate, and the introduced hydrophobic long-chain alkyl greatly reduces the degree of agglomeration of lead titanate, greatly weakening the agglomeration of lead titanate particles, so that the lead titanate has a smaller particle size and a narrower particle size distribution; finally, the modified chitosan is compounded with hexadecyltrimethylammonium bromide and citric acid to obtain a composite surfactant. Through the synergistic effect of the three, the crystallization process is precisely controlled during the lead titanate crystallization process, so that the finally prepared lead titanate has the advantages of uniform particle size distribution, high dispersibility, high purity, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a SEM image of the lead titanate prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1
[0039] A method for preparing electronic grade lead titanate comprises the following steps:
[0040] S1. Add tetrabutyl titanate into ethanol and stir evenly to obtain a tetrabutyl titanate solution with a concentration of 0.8 mol / L;
[0041] S2, adding lead acetate into deionized water, stirring evenly, to obtain a lead acetate solution with a concentration of 0.4 mol / L;
[0042] S3, adding 300 parts by volume of the lead acetate solution in step S2 to 150 parts by volume of the tetrabutyl titanate solution in step S1, then adding a composite surfactant of 3% by mass of the tetrabutyl titanate solution, adjusting the pH to 4, stirring and reacting at 55° C. for 10 hours, and obtaining a sol after the reaction is completed;
[0043] S4, aging the sol in step S3 at 35° C. for 18 h, then drying, grinding, calcining at 650° C. for 2.5 h, then adding 25 times the weight of a 2% disodium EDTA aqueous solution, stirring and immersing for 50 min, filtering, washing 4 times with a 50% ethanol aqueous solution, and drying at 105° C. for 3.5 h to obtain the electronic grade lead titanate.
[0044] Wherein, the preparation method of the composite surfactant described in step S3 comprises the following steps:
[0045] 15g of glutamic acid is added to 900g of deionized water, followed by the addition of 25g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, and after stirring for 40min, 25g of N-hydroxysuccinimide and 55g of hydroxypropyl chitosan are added, and the mixture is reacted at 70°C for 3h. After the reaction is completed, 4g of sodium dodecylbenzene sulfonate and 20g of docosanoic acid are added, and the mixture is reacted at a constant temperature of 85°C for 2.5h. After the reaction is completed, the mixture is concentrated under reduced pressure at 25kPa to 1 / 4 of the volume, and then 4 times the volume of anhydrous ethanol is added for precipitation, followed by filtering, washing and drying to obtain modified chitosan; 70g of modified chitosan, 30g of hexadecyltrimethylammonium bromide and 40g of citric acid are evenly mixed to obtain the composite surfactant.
[0046] from Figure 1It can be seen that the lead titanate prepared in this embodiment has uniform morphology and particle size, with a particle size of approximately 20-30 nm, and has a stable morphology and uniform particle size distribution.
[0047] Example 2
[0048] A method for preparing electronic grade lead titanate comprises the following steps:
[0049] S1. Add tetrabutyl titanate into ethanol and stir evenly to obtain a tetrabutyl titanate solution with a concentration of 0.7 mol / L;
[0050] S2, adding lead acetate to deionized water, stirring evenly, to obtain a lead acetate solution with a concentration of 0.35 mol / L;
[0051] S3, adding 300 parts by volume of the lead acetate solution in step S2 to 150 parts by volume of the tetrabutyl titanate solution in step S1, then adding a composite surfactant of 3% by mass of the tetrabutyl titanate solution, adjusting the pH to 4, stirring and reacting at 55° C. for 10 hours, and obtaining a sol after the reaction is completed;
[0052] S4, aging the sol in step S3 at 35° C. for 18 h, then drying, grinding, calcining at 650° C. for 2.5 h, then adding 25 times the weight of a 2% disodium EDTA aqueous solution, stirring and immersing for 50 min, filtering, washing 4 times with a 50% ethanol aqueous solution, and drying at 105° C. for 3.5 h to obtain the electronic grade lead titanate.
[0053] Wherein, the preparation method of the composite surfactant described in step S3 comprises the following steps:
[0054] 15g of glutamic acid is added to 900g of deionized water, followed by the addition of 25g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, and after stirring for 40min, 25g of N-hydroxysuccinimide and 55g of hydroxypropyl chitosan are added, and the mixture is reacted at 70°C for 3h. After the reaction is completed, 4g of sodium dodecylbenzenesulfonate and 20g of docosanoic acid are added, and the mixture is reacted at a constant temperature of 85°C for 2.5h. After the reaction is completed, the mixture is concentrated under reduced pressure at 25kPa to 1 / 4 of the volume, and then 4 times the volume of anhydrous ethanol is added for precipitation, followed by filtering, washing and drying to obtain modified chitosan; 60g of modified chitosan, 30g of hexadecyltrimethylammonium bromide and 40g of citric acid are evenly mixed to obtain the composite surfactant.
[0055] Example 3
[0056] A method for preparing electronic grade lead titanate comprises the following steps:
[0057] S1. Add tetrabutyl titanate into ethanol and stir evenly to obtain a tetrabutyl titanate solution with a concentration of 0.5 mol / L;
[0058] S2, adding lead acetate to deionized water, stirring evenly, to obtain a lead acetate solution with a concentration of 0.25 mol / L;
[0059] S3, adding 200 parts by volume of the lead acetate solution in step S2 to 100 parts by volume of the tetrabutyl titanate solution in step S1, then adding a composite surfactant in an amount of 2% by mass of the tetrabutyl titanate solution, adjusting the pH to 5, stirring and reacting at 50° C. for 12 hours, and obtaining a sol after the reaction is completed;
[0060] S4, aging the sol in step S3 at 30° C. for 20 h, then drying, grinding, and calcining at 600° C. for 3 h, then adding 20 times the weight of a 1% disodium EDTA aqueous solution, stirring and immersing for 60 min, filtering, washing three times with a 50% ethanol aqueous solution, and drying at 100° C. for 4 h to obtain the electronic grade lead titanate.
[0061] Wherein, the preparation method of the composite surfactant described in step S3 comprises the following steps:
[0062] 10g of glutamic acid is added to 800g of deionized water, followed by the addition of 20g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, and after stirring for 30min, 20g of N-hydroxysuccinimide and 50g of hydroxypropyl chitosan are added, and the mixture is reacted at 60°C for 4h. After the reaction is completed, 3g of sodium dodecylbenzenesulfonate and 15g of docosanoic acid are added, and the mixture is reacted at a constant temperature of 80°C for 3h. After the reaction is completed, the mixture is concentrated under reduced pressure at 20kPa to 1 / 4 of the volume, and then 4 times the volume of anhydrous ethanol is added for precipitation, followed by filtering, washing and drying to obtain modified chitosan; 50g of modified chitosan, 20g of hexadecyltrimethylammonium bromide and 30g of citric acid are evenly mixed to obtain the composite surfactant.
[0063] Example 4
[0064] A method for preparing electronic grade lead titanate comprises the following steps:
[0065] S1. Add tetrabutyl titanate into ethanol and stir evenly to obtain a tetrabutyl titanate solution with a concentration of 1 mol / L;
[0066] S2, adding lead acetate into deionized water, stirring evenly, to obtain a lead acetate solution with a concentration of 0.5 mol / L;
[0067] S3, adding 400 parts by volume of the lead acetate solution in step S2 to 200 parts by volume of the tetrabutyl titanate solution in step S1, then adding a composite surfactant of 4% by mass of the tetrabutyl titanate solution, adjusting the pH to 3, stirring and reacting at 60° C. for 8 hours, and obtaining a sol after the reaction is completed;
[0068] S4, aging the sol in step S3 at 40° C. for 16 h, then drying, grinding, and calcining at 700° C. for 2 h, then adding 30 times by weight of a 3% disodium EDTA aqueous solution, stirring and immersing for 40 min, filtering, washing 5 times with a 50% ethanol aqueous solution, and drying at 110° C. for 3 h to obtain the electronic grade lead titanate.
[0069] Wherein, the preparation method of the composite surfactant described in step S3 comprises the following steps:
[0070] 20g of glutamic acid is added to 1000g of deionized water, followed by the addition of 30g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, and after stirring for 50min, 30g of N-hydroxysuccinimide and 60g of hydroxypropyl chitosan are added, and the mixture is reacted at 80°C for 2h. After the reaction is completed, 5g of sodium dodecylbenzene sulfonate and 25g of docosanoic acid are added, and the mixture is reacted at a constant temperature of 90°C for 2h. After the reaction is completed, the mixture is concentrated under reduced pressure at 30kPa to 1 / 4 of the volume, and then 4 times the volume of anhydrous ethanol is added for precipitation, followed by filtering, washing and drying to obtain modified chitosan; 80g of modified chitosan, 40g of hexadecyltrimethylammonium bromide and 50g of citric acid are evenly mixed to obtain the composite surfactant.
[0071] Comparative Example 1
[0072] A method for preparing electronic grade lead titanate comprises the following steps:
[0073] S1. Add tetrabutyl titanate into ethanol and stir evenly to obtain a tetrabutyl titanate solution with a concentration of 0.8 mol / L;
[0074] S2, adding lead acetate to deionized water, stirring evenly, to obtain a lead acetate solution with a concentration of 0.4 mol / L;
[0075] S3, adding 300 parts by volume of the lead acetate solution in step S2 to 150 parts by volume of the tetrabutyl titanate solution in step S1, then adding a composite surfactant of 3% by mass of the tetrabutyl titanate solution, adjusting the pH to 4, stirring and reacting at 55° C. for 10 hours, and obtaining a sol after the reaction is completed;
[0076] S4, aging the sol in step S3 at 35° C. for 18 h, then drying, grinding, calcining at 650° C. for 2.5 h, then adding 25 times the weight of a 2% disodium EDTA aqueous solution, stirring and immersing for 50 min, filtering, washing 4 times with a 50% ethanol aqueous solution, and drying at 105° C. for 3.5 h to obtain the electronic grade lead titanate.
[0077] Wherein, the preparation method of the composite surfactant described in step S3 comprises the following steps:
[0078] 70 g of hydroxypropyl chitosan, 30 g of hexadecyltrimethylammonium bromide and 40 g of citric acid were uniformly mixed to obtain the composite surfactant.
[0079] Compared with Example 1, the hydroxypropyl chitosan was not modified in this comparative example.
[0080] The nano-barium titanate prepared in Examples 1-4 and Comparative Example 1 was tested, and the grain size was measured by SEM observation. The width of the particle size distribution curve (expressed as D99 / D50, where D99 means that 99% of the particles are smaller than the particle size value) was calculated using minitable software. The larger the D99 / D50 value, the worse the particle size uniformity. The test results are shown in Table 1 below:
[0081] Table 1 Test results of each group of lead titanate
[0082] Group Average particle size / nm purity D99 / D50 Example 1 25.6 ≥99.99wt% 1.24 Example 2 27.3 ≥99.99wt% 1.31 Example 3 32.7 ≥99.99wt% 1.37 Example 4 28.1 ≥99.99wt% 1.29 Comparative Example 1 41.5 ≥99.99wt% 2.68
[0083] As can be seen from Table 1 above, the average particle size of the nano lead titanate prepared by the present invention is between 25-35 nm, the range of D99 / D50 is between 1.2-1.4, it has a narrow particle size distribution, uniform particle size distribution, high purity, and good application prospects.
[0084] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing electronic grade lead titanate, characterized in that: The following steps are involved: S1. Add tetrabutyl titanate into ethanol and stir evenly to obtain a tetrabutyl titanate solution; S2, adding lead acetate into deionized water and stirring evenly to obtain a lead acetate solution; S3, adding the lead acetate solution in step S2 to the tetrabutyl titanate solution in step S1, then adding a composite surfactant, adjusting the pH, stirring and reacting, and obtaining a sol after the reaction is completed; S4, aging, drying, grinding, calcining, and then washing and drying the sol in step S3 to obtain the electronic grade lead titanate; The method for preparing the composite surfactant in step S3 comprises the following steps: Glutamic acid is added to deionized water, followed by 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, and N-hydroxysuccinimide and hydroxypropyl chitosan are added after stirring for 30-50 minutes, and a heating reaction is carried out. After the reaction is completed, sodium dodecylbenzene sulfonate and docosanoic acid are added to carry out a constant temperature reaction. After the reaction is completed, the mixture is concentrated under reduced pressure to 1 / 4 of the volume, and then anhydrous ethanol is added for precipitation, followed by filtering, washing, and drying to obtain modified chitosan; the modified chitosan, hexadecyltrimethylammonium bromide, and citric acid are uniformly mixed to obtain the composite surfactant; The mass ratio of glutamic acid, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide, hydroxypropyl chitosan, sodium dodecylbenzene sulfonate and docosanoic acid is 10-20:20-30:20-30:50-60:3-5:15-25; the temperature of the heating reaction is 60-80°C and the time is 2-4h; the temperature of the constant temperature reaction is 80-90°C and the time is 2-3h.
2. The preparation method according to claim 1, characterized in that: The concentration of the tetrabutyl titanate solution in step S1 is 0.5-1 mol / L.
3. The preparation method according to claim 1, characterized in that: The concentration of the lead acetate solution in step S2 is 0.25-0.5 mol / L.
4. The preparation method according to claim 1, characterized in that: In step S3, the volume ratio of the tetrabutyl titanate solution to the lead acetate solution is 100-200:200-400; the amount of the composite surfactant added is 2-4% of the mass of the tetrabutyl titanate solution; the pH is 3-5, the temperature of the stirring reaction is 50-60°C, and the time is 8-12h.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the modified chitosan, hexadecyltrimethylammonium bromide and citric acid is 5-8:2-4:3-5.
6. The preparation method according to claim 1, characterized in that: The aging temperature in step S4 is 30-40°C and the time is 16-20h; the calcination temperature is 600-700°C and the time is 2-3h.
7. The preparation method according to claim 1, characterized in that: The washing process in step S4 is: add 20-30 times the weight of lead titanate to a 1-3% disodium EDTA aqueous solution, stir and immerse for 40-60 minutes, filter and then wash 3-5 times with a 50% ethanol aqueous solution; the drying temperature is 100-110°C and the drying time is 3-4h.
8. An electronic grade lead titanate prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method for preparing high-purity lead titanate
CN102303903A
Preparation method of PZT (lead zirconate titanate) piezoelectric aerogel
CN108467059A